PENGEMBANGAN FILM ANIMASI 3 DIMENSI "Tude The Movie – Petualangan Si Rina (Festival Layang-Layang)" - I Putu Ade Widiyantara; Padma Nyoman Crisnapati; I Made Gede Sunarya; I Gede Mahendra Darmawiguna (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2015)
The development of three-dimensional animated film "Tude The Movie – The Adventure of Si Rina (Kite Festival)", is the story of part 4 from 5 parts contained in the animated film ―Tude The Movie‖, this section tells where Tude, Rina and friends arrived in the second area of their destinations, which is Padang Galak beach, they had planned to watch the largest kite festival in Bali which is only held once a year, the participants of this festival came from all regions in Bali, there are also some types of kites that are following the contest such as Janggan (bird-shaped), Bebean (fish-shaped) and others New Creation. In this story Tude, Rina and his friends met with Made, and Made told them that bird which is carried by Rina is a rare species bird, that is Jalak Bali bird. Then, they were invited to participate on this contest. In the part of this film also as a medium to introduce Balinese kite culture, on some parts of the film also contains some moral messages such as, creativity in creating Balinese kites, teaches us to always try and work together to achieve a goal (in this case flying up the large kite and win), the preservation of nature by doing a bird rescue although we don’t know that is a rare bird, and it's not always the traditional ones is old-fashioned and such a boring thing. The aim of this study were: 1) Designing three-dimensional animated film "Tude The Movie-The Adventure of Si Rina (Kite Festival)‖. 2) Implementing three-dimensional animated film "Tude The Movie-The Adventure of Si Rina (Kite Festival)‖.In this 3D animation film making, we use block diagrams methods. This Block diagram describes the steps of making 3-D animated film Tude The Movie : Petualangan Si Rina (Festival Layang-layang) from start to finish. The steps In the block diagram is divided into three (3) main phases: 1) Pre-Production (Story idea, Script Writing / Sipnosis, Output Format Setting, Character Design, Image Design, and Making Storyboard), 2) Production (Modelling, Texturing, Ringging, Skining, Acting / Animation, Lighting, and Rendering), 3) Post Production (Recording and Merger process).The result is 3-dimensional animation format DVD. The film is expected to provide an exciting spectacle and educational for the audience, especially children. So with this young generation’s animations development can make local television interesting and no longer have to import 3D animation from other countries.